Penggunaan Media Powtoon untuk Meningkatkan Hasil Belajar Matematika dengan Teknik Mengajar - Ana Quthratun Nada; Deni Indrawan (FONDATIA, 2023)
This study aims to determine the increase in student learning outcomes in mathematics with the application of powtoon media using teaching techniques. This research approach is a qualitative approach to the type of research is classroom action research. The focus of this research is the focus of mathematics learning outcomes. This research was conducted at MI Al Huda Yogyakarta. which totaled 24 students. This research was conducted in three cycles. Each cycle includes the stages of planning, implementing, observing and reflecting. From the implementation obtained data collected by observation techniques, learning achievement tests and documentation. The results of the study concluded that the use of powtoon media can improve the mathematics learning outcomes of class III MI Al Huda students, especially in terms of multiplication with the memory cycle technique. This increase occurs in each cycle. For example in cycle 1 as many as 12 students are said to have completed. Whereas in cycle II there were 19 students who were said to be complete and finally in cycle III all students were said to be complete. Of all these cycles experienced an increase in terms of average, such as the first cycle of 65.41, the second cycle of 71.45 and the third cycle of 81.04.